Specialized Military Journalism in the System of Mass Communication During the Russian-Ukrainian War (2014-2022): Comparative Analysis of World and Ukrainian Mass Media - Kosiuk, Oksana M. (Europe Our House, 2022)
The article gives an analysis of world military publications and militarized journalism in comparison with the Ukrainian comparables in historical retrospective view and in the context of Russia's full-scale invasion of Ukraine, which is still ongoing. Special attention is paid to international military-focused media standards and specific military (mainly print) mass media: Stars and Stripes, Milli təhlükəsizlik və hərbi elmlər, Narodna Armiia (People's Army), Army Inform, Officer of Ukraine, on occasion – The Washington Post, The New York Times and others. In the process of research, it was found out that military journalism has almost completely transformed into universal journalism. And for some reason, specialized printed editions of military focus have closed down in recent years. And if in Ukraine it is associated with the denationalization of the mass media, then abroad, it is most likely connected with the processes of digitalization and the separation of journalism from ideologies and state policies. As a result, the remaining military mass media are also changing their format, approaching global brands such as The Washington Post, The New York Times, Le Mond. However, this does not prevent them from putting information and analytics about Russia's war against Ukraine in the foreground and highlighting key points as reality and the principle of objectivity require. And although the Ukrainian mass media in this regard are far from ideal, their ideological bias should be attributed to the war, an organically inherent ritual model of communication and still a close connection with the socialist past. Since military journalism is currently working in extreme conditions, it is difficult to draw comprehensive conclusions, but it is already clear that specialized military media are relevant and promising for scientific research.
Keywords: military mass media; war; Ukraine; the US; Eurasia; propaganda; standard